Increased Expression of Ecto-NOX Disulfide-thiol Exchanger 1 (ENOX1) in Diabetic Mice Retina and its Involvement in Diabetic Retinopathy Development - HUANG, CHUEN (In Vivo, 2019)
Background/Aim: Diabetic retinopathy (DR) is a type of retinal damage caused by a complication of diabetes and is a major cause of blindness in working-age adults. Ecto-NOX disulfide-thiol exchanger 1 (ENOX1) is a member of the ecto-NOX family involved in the plasma membrane electron transport pathway. This study aimed to investigate the role of ENOX1 in the development of DR. Materials and Methods: Human retinal endothelial cells (HRECs) and human retinal pigment epithelial cells (HREpiCs) exposed to a high concentration (25 mM) of D-glucose and type 2 diabetes (T2D) mice (+Lepr(db)/+Lepr(db), db/db) with retinopathy were used as models to determine the ENOX1 expression levels there. Results: Our results showed that ENOX1 expression levels did not significantly change in both HRECs and HREpiCs under hyperglycemic conditions for 48 h. Nevertheless, ENOX1 expression increased significantly in T2D mouse retinas, particularly in the photoreceptor layer, compared to the control mouse retinas. Conclusion: Different retinal ENOX1 expression in T2D mice and control mice suggested that ENOX1 may be involved in DR development.